Teachers' Perceptions on the Development of Project-Based Learning Program for Vegetable Waste Treatment to Increase Students’ Scientific Creativity - Anadia Rosaria; Noor Fadiawati; Chansyanah Diawati (Postgraduate, University of Mataram, 2023)
Conventional learning that is still applied by teachers causes the quality of human resources in Indonesia to be still relatively low. Teachers should apply learning that can increase the skills needed in 21st century, one of these skills is scientific creativity. In this study to find out the teacher's perspective regarding project-based learning of vegetable waste processing to increase e students' scientific creativity. The research method used is a mixed method with Sequential Explanatory Design. Data collection was carried out by distributing questionnaires to 10 science teacher respondents at junior high schools in Tanggamus. The collected data were analyzed using descriptive analysis. The results of the study show that there are still many teachers who apply the lecture method and 100% of the teacher respondents have never implemented project-based learning and have never solved real problems such as processing vegetable waste in science learning. In fact, the problem that occurs in East Kotaagung District is vegetable waste that is not properly processed. As many as 100% of teacher respondents did not know students' scientific creativity, so they had never been able to increase students' scientific creativity. Based on the teacher's perception of these findings, it can be concluded that it is necessary to develop a learning program based on a vegetable waste processing project to increase students' scientific creativity.